THE USE OF FLASHCARD TO IMPROVE STUDENTS’ PARTICIPATION ON SPEAKING ACTIVITIES FOR THE EIGHTH GRADERS OF MTS AL HIDAYAH WEDORO GLAGAH LAMONGAN - Yuliana Racmalia; Bariqotul Hidayah (J-Shelves of Indragiri (JSI), 2024)
This study analyzes the use of flashcards to improve student participation in speaking for eighth graders at MTs Al Hidayah in the second semester of the 2023/2024 school year. The subjects of this study were seventeen eighth graders. This study used classroom action research. There are two cycles, each cycle consists of two meetings. This study used observation sheets, field notes, and questionnaires to collect data. In the first cycle, 41% of students passed with a low passing score. The figure was still with 34% of students below the set minimum score of 75%. Therefore, the first cycle was far from successful. In the second cycle, 82% of students achieved the lowest required passing grade, as well as passing with the minimum grade with a percentage of 75% of students. Therefore, the students had reached the success criteria in the second cycle. The results of this study show that the use of flashcards as a medium for learning speaking can effectively improve participation in students' speaking activities.